Uso de la N-acetilcisteina en amenaza de parto pretérmino causada por infección de vías urinarias y/vaginosis, en las pacientes hospitalizadas en el servicio de ginecología y obstetricia del Hospital General Isidro Ayora de Loja. - Castillo Vásquez, Maritza Paulina. (2014)
Preterm birth affects approximately 10% to 15% of all births in recent decades continues to be the major cause of neonatal morbidity and mortality. Because of the high incidence of urinary tract infection and bacterial vaginosis, as triggers of a threat of preterm delivery, the research objectives was to determine the efficacy of N-acetylcysteine as an adjunct in the treatment of preterm labor caused by infection urinary tract and / or vaginosis; its effect on the prolongation of pregnancy until week 37 and to evaluate the percentage of hospital readmission. The study was conducted in the service of Gynecology and Obstetrics, General Hospital Isidro Ayora Loja, from January to April 2014. Study of quasi-experimental randomized, placebo-controlled study involving 63 pregnant women with preterm labor that met the criteria inclusion and exclusion; we divided the patients into 2 groups, one group received N-acetylcysteine 0.6g / day / 10 days, and another group received the same way a placebo, added to the corresponding antibiotic and tocolytic therapy. Prenatal controls were performed subsequent to delivery. From the results obtained N-acetylcysteine, prolonged gestation period, reaching an average of 37.19 weeks; whereas in the placebo group reached the mean is 36 weeks; readmission in the N-acetylcysteine group 28.1% and 45.2% in the placebo group. So it was considered that the use of N-acetylcysteine is effective in prolonging pregnancy with preterm labor associated with the two pathologies, urinary tract infection (37 weeks) and bacterial vaginosis (36.7 weeks), thus reducing the reentry hospital by 72%. Therefore it is recommended to increase the use of N-acetylcysteine as an adjunct in the treatment of these patients.